Early Marriage According to the Views of Muhammadiyah Figures and Nahdlatul Ulama Leaders (Case Study in Fisherman Village Communities, Medan Marelan District) - Desi Handayani Daulay; Amal Hayati; Rahmad Efendi (Fakultas Hukum Dehasen, 2023)
In this modern era, early marriage still occurs in many regions and regions in Indonesia. For example, a phenomenon that occurs in one of the villages in the city of Medan, namely in Labuhan Village or Fisherman's Village, Medan Marelan District. Many teenagers who do early marriage in the Fisherman Village, Medan Marelan District. Between the ages of 15-17 years, the time span is from August 2021 to January 2022. There are 5-10 teenagers who do early marriages that occur in the Fisherman Village, Medan Marelan District. From the description above, the researcher is interested in discussing the thesis with the title